TITLE: THE ROLE OF ISLAMIC CIVILIZATION IN THE ARCHITECTURE AND DECORATIVE ARTS OF CENTRAL ASIA - Abdumannobova Mohidil (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article examines the influence of Islamic civilization on the development of architecture and applied arts of the peoples of Central Asia. The article highlights the philosophical meanings of floral (islimi) and geometric (girih) patterns, the symbolism of blue color, and the spiritual significance of architectural monuments. Additionally, the harmony of Islamic values with aesthetic beauty is analyzed through the examples of historical landmarks.